METODE THREE STEP INTERVIEW UNTUK KETERAMPILAN BERBICARA BAHASA JERMAN SISWA KELAS XI IBB SMAN 3 SIDOARJO - SEPTI TAMARA, THALIA (LATERNE, 2018)
In language learning there are four skills, one of which is the speaking skill. Speaking skills are language skills aimed at expressing ideas, ideas for the purpose of communication with others. One of the obstacles that students experience when learning is the difficulty in speaking German. Often learners feel afraid and embarrassed when given the task to appear and speak in front of his friends and less skilled becauses less speaking practice. Three Step Interview Method can be one alternative to speaking practice. The student become more daring/ brave and free to speak German, because the other person is his friend. Three Step Interview is a learning method consisting of three stages of activity that the students consist of two people alternately interview each other, then report the results of interviews with their partner. The formulation of the problem in this study is, how the learning outcomes of speaking skills of students class XI IBB SMAN 3 Sidoarjo by using the Three Step Interview Method. The purpose of this research is to describe the learning achievement of learner?s speaking skill by using Three Step Interview Method. The research instrument is in the test of speaking skill of question and answer interview. Research data obtained from the results of the value of learners for three times the test. Then the results of the values are analyzed using the rubric of the assessment of speech skills. The results showed that the value of learners increased, some others remain and decline. a total of 17 people experienced an increase in value from the first test to the third test. Then as many as 4 people get the same score on the second test and the third test. Then a number of 9 students who experience a decline in value from the second test to the third test. Based on research, half of the students in class has increased after applied Method. So the Three Step Interview method can be an alternative method to practice speaking skills. Keywords: Learning outcomes, Speaking skills, Three Step Interview Method